Electroanalytical determination of 4-nitrophenol by square wave voltammetry on diamond electrodes - Pedrosa,Valber de A. (2003)
The anodic voltammetric behavior of 4-Nitrophenol on a Boron-doped diamond electrode in aqueous solution has been studied using square wave voltammetry. After optimization of the experimental conditions, that model molecule was analyzed in pure water solutions using a Britton-Robinson buffer with pH 6.0 as the supporting electrolyte. Oxidation occurs at 1.0 V vs. Ag/AgCl in an irreversible two-electron process controlled by adsorption of the species. The detection limit (DL) obtained was 2.8 mug L-1. This result was comparable to that obtained from reduction of the molecule at -0.8 V vs. Ag/AgCl under the same experimental conditions (DL = 4.2 mug L-1). Both DL values are within the limits required by the legislation for drinking water (30 mug L-1). The combination of square wave voltammetry and diamond electrodes has proved to be an interesting and desirable alternative for the analytical determination of organic molecules.